Proceedings of the International Conference on Transformations in Engineering Education ICTIEE 2014 - Natarajan, R.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
This book comprises the proceedings of the International Conference on Transformations in Engineering Education conducted jointly by BVB College of Engineering & Technology, Hubli, India and Indo US Collaboration for Engineering Education (IUCEE). This event is done in collaboration with International Federation of Engineering Education Societies (IFEES), American Society for Engineering Education (ASEE) and Global Engineering Deans' Council (GEDC). The conference is about showcasing the transformational practices in Engineering Education space.
INVITED PAPERS: Panel Discussion: Transformations in Engineering Education Globally -- The Important Tool for the Transformation in Global Engineering Education – Mobility -- Adopting MOOCs for Quality Engineering Education in India -- Outcomes-Based Accreditation and ABET -- Present Status and Challenges Ahead for Engineering Education – Global and National Perspectives -- Innovation & Entrepreneurship in Engineering Education -- Attributes of Engineers and Engineering Education for the 21st Century World -- Engineers without Borders -- Pedagogy Training and Certification for Faculty -- Transforming Engineering Education: The Role of Engineering Educators in Making Meaningful Change -- ORAL PAPERS: Application Based Approach of Teaching Digital Signal Processing to a large Class in the Context of an Affiliated System -- Keyword Based Search and Ranking in NPTEL Lecture Videos -- Mini Projects – A New Concept of Transformation of Teaching-Learning Process -- Success Story of Industry Institution Collaboration for Enhancing Teaching Learning Experience -- Overlapped Concepts Pedagogy for Advanced Computer Architecture -- Learning made Easy-by LABVIEW Software tool -- Contemporary Access to Engineering Education and Research Using Interactive Knowledge and Modeling Techniques -- Puzzle Based Learning: A Joyful Learning Strategy in Automotive Engineering Education -- Improving Class Room Dynamics through Teaching Learning (academic) Audit -- IT Education and Team Based Learning -- Academic Information Management System Using Open Source Programming Tools and Technologies -- Designing Curriculum of IT: A Journey -- Essential IT Skills to Learning Community for Industry Readiness -- Benefits of Cloud Computing in Education during Disaster -- Technology Enhanced Learning through ICT Tools Using Aakash Tablet -- Impact of IUCEE on Institutional Performance: A Case Study of Rajarambapu Institute of Technology -- Green Electronics Design: Curriculum, Content and Learning for Engineering -- Should we have Compulsory “Engineering Ethics” Course for Engineers? Why should it be? -- Tracking Lab Activity in Technical Education System: A Case-study at the Guru Nanak Institutions (India) -- Curriculum Re-design in Higher Education Using QFD – A Case Study -- Evolution of Engineering Education in India -- “Millimeter Techniques for Kilometer Benefits” Creating Excitement in CAED Classroom -- Program Outcome Attainment through Course Outcomes: A Comprehensive Approach -- The Education Design Shop: A Case Study on Education Reform through Design Thinking -- Inquiry Based Guided Learning to Enhance Interest and Higher Order Thinking in Engineering Graduates: A Computing Education Perspective -- Measuring the Impact of Design Fixation on Indian Engineering Students -- PPP – A Paradigm for Online Education in Engineering Colleges -- Innovative Method of Teaching Digital Signal Processing Using Ubiquitous Learning Strategies -- Transforming Engineering Students into Industry Ready Professionals -- Impact Analysis of Students’ Learning Styles in Effective Planning & Delivery of Courses – A Case Study of Data Mining Course -- WiMAX in Education: A Wireless Networking Lab Design -- Creating an Integrated Learning Experience within Curriculum Threads through Mini-Projects -- Experience of Using Felder-SOLOMAN Index of Learning Styles -- Teaching Reform through Model Building in Theory of Machine Course -- Application of Design of Experiments (DOE) in Course Project -- SUCC Tool Kit: An Activity in Data Structure laboratory -- Open End Activity (OEA): An Experience in Computer Graphics Laboratory -- Leveraging Technology in Outcome Based Education -- Multidisciplinary Approach to Product Design and Realization -- Contextual Integration of Industrial & Production Engineering Curriculum -- Automotive Electronics: Learning through Real-World Problem Based Case Studies -- Pedagogical Transformation in Heat and Mass Transfer Laboratory Course of Undergraduate Mechanical Engineering Programme -- Enhanced Learning through Self Study Component in Engineering Education -- Mapping Graduate Attributes of NBA with the Program Outcomes of the ABET/OBE to Establish Consistency between the Two -- Integrated Experience: Through Project-Based Learning -- Problem Identification through Literature Survey: A Course Project Activity to Satisfy Accreditation Requirements -- Attainment of Professional Outcome by Active Learning Method -- A Case Study on Improving Students’ Conceptual Understanding in Engineering Courses -- 21st Century Classroom Engineering – Designing Effective Learning Environments: A Conceptual Case Study -- Project Based Learning in Laboratories Using Open Source Technologies: Case Study of a Frugal Approach -- A Study on Methodology and Implementation of Flipped Classroom Teaching For Engineering Courses Curriculum Design and Instructional Practices for Experiential Learning -- POSTERS: Moving Towards Experiential Learning -- Smart Assessment of Program and Course Outcome with Students' Objectives -- Technology Enhanced Teaching Learning Using Palm Devices -- Transformation of Engineering Education Using Quality Circle Approach -- Personal Transformation from Teacher to a Learning Facilitator: A Case Study -- Strategic Planning for an Engineering Institute – A Case study of Rajarambapu Institute of Technology, Sakharale -- Prominent Assessment of Students Learning and Statistical Analysis of Quizzes -- Engineering Education and Employability: Our Commitment -- Application of Curriculum Innovation for Production Management Subject -- Soft Skill Training through Cooperative Learning: A Case Study -- BLOG Based Student Lab Assignment & Assessment -- Overview of Effective and Efficient Learning Model PBL - Project Based Learning -- A Global Knowledge Mining Hub - Technology Enhanced Learning -- Project Based Learning – An Enhanced Approach for Learning in Engineering -- An Effective Lab in Digital Signal Processing -- Open Assessment Method for Better Understanding of Student’s Learnability to Create Personalised Recommendations -- Learning Outcomes in Engineering Education: A Review of Experimentation at Walchand Institute of Technology, Solapur -- Overview of Accreditation System and Investigations of Assessment Methods/Techniques for Quality Assurance of Engineering Education -- The Institutional Leadership of JNTUK System in Embracing New Paradigms in Engineering Education -- Developing Effective Industry Partnerships to Pro-mote Learning and Entrepreneurship -- Role of Industry-Institute-Interaction to Promote Education and Entrepreneurship -- Technology: A Source of Supplement to the Teaching and the Process of Learning in Higher Education -- Indian Technical Teaching Service (ITTS) – A Proposal to Improve Quality of Engineering Education -- Electronic System Design, Manufacturing and Human Resource -- Efficient Teaching Aid: Self Learning Models -- Developing Innovation among Under-Graduate Students -- The Innovative Cloud-based Solution for Classroom Transformation -- Group - Assignment writing in Engineering: Some Preliminary findings -- IPython Notebook for Teaching and Learning -- A LabVIEW Based Laboratory Experience of Real Time Embedded Concepts -- A Framework for Curriculum Design of Data Structures and Design of Algorithms Course (DSDA) -- Assessment of Program Outcome by Open-Ended Experiment in Enzyme Technology Laboratory Course -- Introduction of Chapter “How Stuff Works” and Course Seminar in Elements Of Mechanical Engineering -- Outcome based pedagogical approach for Energy conversion laboratory course of Mechanical Engineering UG Programme -- A Comprehensive Method For Defining and Assessing Programme Outcome – A Lifelong Learning Through Direct Assessment Techniques -- An Attempt to Bridge the Gap Between Industry and Academia – An Experience -- Effective Teaching of Digital Electronics for Undergraduate Students Using a Free Circuit Simulation Software-SEQUEL -- Theme Based Capstone Projects and Programme Outcome Evaluation: A Case Study -- Importance of Research at Undergraduate level.
Keywords: Engineering—Vocational guidance; Higher education; Professional education; Vocational education; Job Careers in Science and Engineering; Higher Education; Professional & Vocational Education